Quantification of cellular antigens by means of flow cytometry and its role in rheumatology - A. Cauli; G. Dessole; G. Passiu; A. Mathieu (PAGEPress Publications, 2011)
Flow cytometric analysis is a technique wich allows not only phenotypical characterization of cellular subsets but also allows quantitation of cellular antigens. In this paper we summarize the Molecules of Equivalent Soluble Fluorochromes (MESF) units and the Antibody Binding Capacity (ABC) methods.